Using a Universal Design for Learning Checklist to Teach Secondary Transition Skills. (November 2018) - Bartholomew, Audrey L.; Griffin, Nancy
The authors present a tool teachers can use to modify their instruction so that it is based on universal design and includes secondary transition topics and skills. This checklist includes Universal Design for Learning (UDL) checkpoints and prompts teachers to go through a set of guiding questions that focus on both UDL and secondary transition. Also included in the article are examples of how a general education teacher can use the checklist to design inclusive instruction around secondary transition topics.